Implications of Business Certainty for Plantation Companies on Land Release PolicieshImplications of Business Certainty for Plantation Companies on Land Release Policiesh - M. Iqbal Asnawi; Radhali; Verianto Dwikaprio Pane; Agung Ibrahim Hasibuan (Mahadi: Indonesia Journal of Law, 2026)
This study analyzes the policy on the partial release of plantation land through the plasma partnership scheme and the Agrarian Reform Object Land (TORA) program from the perspective of legal certainty and the protection of business actors’ rights. The issue arises when the obligation to release land is imposed without a clear compensation mechanism, while companies have lawfully obtained Cultivation Rights (HGU) and invested long-term capital based on the granted land area and duration. This research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that land release through plasma schemes and TORA does not explicitly regulate fair compensation, thereby potentially creating legal uncertainty and disrupting the investment climate. Normatively, any reduction or acquisition of land rights for public purposes should be carried out through land procurement or revocation mechanisms that require just and adequate compensation. The study concludes that it is necessary to reformulate land release policies based on proportionality and constitutional balance principles to ensure that agrarian reform remains aligned with Pancasila values while safeguarding justice and sustainable investment in the plantation sector.